(3GdMeGjI GdLfGFjI dGSJFUGd hRQY GdCYVGA GdHTQjI (B:s - (3agej, OjfG YHO GdYRjRs ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI,s, 2016)
(3jJfGhd GdcJGH GdBJj (B: (3aUd JegjOj(B: (3MQeI LSe GdEfSGf(B. (3GdeHMK GdChd (B: (3GdMb aj SdGeI GdLSe(B. (3GdeWdH GdChd (B: (3eVehf GdMb aj SdGeI GdLSe(B. (3GdeWdH GdKGfj (B: (3MeGjI GdMb aj SdGeI GdLSe(B. (3GdeHMK (B: (3eTQhYjI YedjGJ GSJFUGd hRQY GdCYVGA GdHTQjI(B. (3GdeWdH GdKGfj (B: (3GdJfXje GdbGfhfj dYedjGJ GSJFUGd hRQY GdCYVGA GdHTQjI(B. (3GdHGH GdChd (B: (3GdMeGjI GdLfGFjI dGSJFUGd hRQY GdCYVGA GdHTQjI ef GdCMjGA(B. (3GdaUd GdChd (B: (3TQhW GSJFUGd hRQY GdCYVGA GdHTQjI ef GdCMjGA(B. (3GdeHMK GdChd (B: (3GdVQhQI dGSJFUGd hRQY GdCYVGA GdHTQjI(B. (3GdeWdH GdChd (B: (3GdNWQ(B. (3GdeWdH GdKGfj (B: (3GdTQhW GdhGLH JhGaQgG aj GdVQhQI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3RQY GdCYVGAs -- (3bhGfjf hJTQjYGJs; (3fbd GdCYVGAs -- (3bhGfjf hJTQjYGJs; (3LSe GdEfSGfs -- (3bhGfjf hJTQjYGJs; (3GdJHQY HGdCYVGAs -- (3bhGfjf hJTQjYGJs; (3GdeSFhdjI GdLfGFjI ddCWHGA s; (3GdJLGQH GdHTQjI aj GdWHs -- (3bhGfjf hJTQjYGJ s; (3fbd GdCfSLI hGdCYVGAs; (3GdbGfhf GdLfGFjs; (3RQGYI GdCYVGAs; (3GdehJ GdLSOjs; (3GdNdGjG GdLPYjIs; (3GdCYVGA GdHTQjIs; (3Mbhb GdEfSGfs